SAT0616 DIETARY HABITS OF SIX AUTOIMMUNE DISEASES IN THE SPANISH POPULATION: A CROSS-SECTIONAL STUDY. (June 2019) - Julià, Antonio; Martinez, Sergio Hilario; Tornero, Jesús; Cañete, Juan D.; Fernandez-Nebro, Antonio; Blanco, Francisco; Rodríguez, Jesús; López-Longo, Francisco J.; Fernández-Gutiérrez, Benjamín; Gratacós, Jordi; Pérez Venegas, José Javier; Pérez, Carolina; et al.
Abstract : Background: In the last years multiple genetic variants have been associated with autoimmune disease (AD) risk. However, much less is known on the association with important environmental factors like diet. Objectives: The objective of the present study is to characterize the dietary patterns of six prevalent ADs, including rheumatoid arthritis (RA), psoriatic arthritis (PsA) and systemic lupus erythematosus (SLE). Methods: A cross-sectional cohort of 11, 621 individuals from Spain encompassing 1, 949 RA, 2, 186 psoriasis (PS), 1, 437 PsA, 699 SLE, 1, 415 ulcerative colitis (UC), 1, 952 Crohn's disease (CD) and 1, 983 healthy controls, was recruited by the IMID-Consortium. The weekly consumption frequency of main food categories was recorded, together with drinking habits and smoking status. Multivariate linear models were used to test for association while adjusting for confounders. Results: Patients with AD targeting the digestive system showed the largest differences in comparison to controls. In the rheumatic ADs several food categories were also found to be consumed differently compared to controls. SLE had a high consumption of sweets and pastries, and RA ate more fruit and bread/wholegrain foods and less meat and cold cuts compared to controls. In PsA the dietary pattern differences with controls where milder, and non-overlapping with psoriasis. Disease activity was significantly associated with specific food categories in CD, UC and PS, mildly in RA and SLE, and PsA showed no association. High smoking cessation rates were observed in UC, CD and SLE, but not in Ps, RA and PsA. Tea/coffee and alcohol consumption was low in all ADs compared to controls. Conclusion: Our results show previously unreported associations with dietary habits in rheumatic ADs. Disclosure of Interests: Antonio Julià: None declared, Sergio Hilario Martinez: None declared, Jesús Tornero: None declared, Juan D. Cañete: None declared, Antonio Fernandez-Nebro: None declared, Francisco Blanco: None declared, Jesús Rodríguez: None declared, Francisco J López-Longo: None declared, Benjamín Fernández-Gutiérrez: None declared, Jordi Gratacós: None declared, José Javier Pérez Venegas: None declared, Carolina Pérez: None declared, Rubén Queiró Silva: None declared, Alejandro Olive: None declared, Mercedes Alperi-López: None declared, Carlos A. Montilla-Morales: None declared, Jose Luis Andreu: None declared, Juan Carlos Torre-Alonso: None declared, M Ángeles Aguirre-Zamorano: None declared, Héctor Corominas: None declared, Paloma Vela Casasempere: None declared, Victor Martinez Taboada : None declared, Sara Manrique Arija Speakers bureau: ABBvie, MSD, Janssen, Lillly, Roche, Pfyzer, Novartis., Joan Miquel Nolla: None declared, Isidoro González-Álvaro: None declared, Santiago Muñoz-Fernández: None declared, Jose Luis Marenco Speakers bureau: abbie, pfizer, novartis, janmsen, Carlos M. González: None declared, Antonio Zea: None declared, Maria Lopez Lasanta: None declared, Daniel Roig: None declared, Jose M Pego-Reigosa: None declared, Mireia Lopez Corbeto: None declared, Pedro Zarco-Montejo: None declared, Mercedes Freire González: None declared, Alba Erra: None declared, Elvira Diez Alvarez: None declared, Santos Castañeda Consultant for: Amgen, BMS, Pfizer, Lilly, MSD, Roche, Sanofi, UCB, Esther Rodríguez Almaraz: None declared, Alicia García: None declared, Patricia Carreira: None declared, GEORGINA SALVADOR ALARCON: None declared, Cesar Diaz Torne Consultant for: Grünenthal, Speakers bureau: Grünenthal, Ricardo Blanco: None declared, Alfredo Willisch Dominguez: None declared, José Antonio Mosquera Martínez: None declared, Simon Sánchez Fernandez: None declared, Julio Ramirez: None declared, Sara Marsal: None declared